Using the Technology Acceptance Model to Identify Factors That Predict Likelihood to Adopt Tele-Neurorehabilitation - Klaic, Marlena; Galea, Mary P. (Frontiers in Neurology, 2020)
Tele-neurorehabilitation has the potential to reduce accessibility barriers and enhance patient outcomes through a more seamless continuum of care. A growing number of studies have found that tele-neurorehabilitation produces equivalent results to usual care for a variety of outcomes including activities of daily living and health related quality of life. However, there is little evidence regarding feasibility and acceptability of tele-neurorehabilitation. Furthermore, few published studies on tele-neurorehabilitation use a theoretical framework to guide the implementation. There is strong evidence to suggest that interventions guided by an appropriate theoretical model are more likely to be successful and sustain practice change. The technology acceptance model (TAM) was developed 20 years ago and is one of the most widely used theoretical frameworks for predicting an individual’s likelihood to adopt and use new technology. The TAM3 further built on the original model by incorporating additional elements from human decision making such as computer anxiety. In this perspective, we use the TAM3 to explore the determinants of likely adoption of tele-neurorehabilitation by both stroke survivors and prescribing clinicians. We present evidence from studies on tele-neurorehabilitation that suggest computer self-efficacy and computer anxiety are significant predictors of an individual’s likelihood to use tele-neurorehabilitation. Understanding what factors are critical to support or hinder uptake of tele-neurorehabilitation can assist in translatability and sustainable adoption of this technology. If we are to shift tele-neurorehabilitation from the research domain to become a mainstream health sector activity, key stakeholders must address the barriers that have consistently hindered adoption.